Higher skin sympathetic nerve activity as a potential predictor of overactive bladder in females refractory to oral monotherapy - Yu‐Chen Chen; Hao‐Wei Chen; Tien‐Chi Huang; Chien‐Hung Lee; Ting‐Yin Chu; Yung‐Shun Juan; Yu‐Peng Liu; Wei‐Chung Tsai; Wen‐Jeng Wu (Kaohsiung Journal of Medical Sciences, 2024)
Abstract This study investigates predictors of unsatisfactory outcomes in female overactive bladder (OAB) patients treated with oral monotherapy by analyzing skin sympathetic nerve activity (SKNA) using a novel “neuECG” method. The study included 55 newly diagnosed female patients with idiopathic OAB, autonomic function was evaluated using neuECG before treatment initiation, and validated OAB questionnaires and urodynamic studies were administered. Initial monotherapy was administered for the first 4 weeks, with non‐responders defined as patients not achieving satisfactory symptom relief and requiring further treatment. Responders (n = 32) and non‐responders (n = 23) had no significant differences in baseline characteristics or urodynamic parameters; however, non‐responders exhibited significantly higher baseline average SKNA (aSKNA) (1.36 ± 0.49 vs. 0.97 ± 0.29 μV, p = 0.001), higher recovery aSKNA (1.28 ± 0.46 vs. 0.97 ± 0.35 μV, p = 0.007), and a lower stress/baseline ratio of aSKNA (1.05 ± 0.42 vs. 1.26 ± 0.26, p = 0.029). Baseline aSKNA had the highest predictive value for monotherapy refractoriness in OAB (AUROC = 0.759, p = 0.001), with an optimal cut‐off point of >1.032 μV. These findings suggest that elevated pre‐treatment aSKNA can predict resistance to oral monotherapy in OAB, warranting close monitoring and proactive treatment strategies for patients with high aSKNA.